PENGIDENTIFIKASIAN KARAKTERISTIK RESERVOIR SEBAGAI DASAR PENENTUAN ZONA PROSPEK DI FORMASI TUALANG, LAPANGAN “KHF”, CEKUNGAN SUMATRA TENGAH - Soesanto, Edy; Kosasih, Arif Wibowo; Sukma, Vandra Firmasyah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Tualang Formation which is the research target is located in the “KHF” Field, Central Sumatra Basin. Petrophysical analysis was carried out on three wells using data from well log, core, and mudlog to determine reservoir characteristics so that prospect zones can be determined. Reservoir in Tualang Formation is shaly sandstone which contains a lot of clay minerals. The clay content will affect the characteristics of the reservoir. Calculation results of shale volume, effective porosity, and water saturation show quite high values with cut-off of shale volume 60%, porosity 10%, and water saturation 65%. The prospect zone on the KHF-1 at 3,214-3,258 ft, KHF-2 at 3,272-3,318 ft, and KHF-3 at 3,210- 3,244 ft, 3,320-3,386 ft, and 3,430-3,452 ft. The best reservoir candidate is tidal channel facies because it is evenly distributed in all three wells and is the thickest compared to other facies. The average value of each tidal channel facies parameter in the “KHF” field is 49.9% for shale volume, 11.4% for porosity i-ISSN: 2597-4033 Vol. 7, No. 1, Februari 2023 Identifikasi Karakteristik Reservoir untuk Penentuan Zona Prospek Melalui Analisis Petrofisika pada Formasi Tualang, Lapangan “Khf”, Cekungan Sumatra Tengah 1080 which is classified as enough according to Koesoemadinata (1980), and 60.2% for water saturation. The thickness of the reservoir ranges from 21.5-29 ft with a gaseous fluid content